The extremophile Anoxybacillus sp. PC2 isolated from Brazilian semiarid region (Caatinga) produces a thermostable keratinase. (29th June 2020) - Reis, Sharon V. dos; Beys‐da‐Silva, Walter O.; Tirloni, Lucas; Santi, Lucélia; Seixas, Adriana; Termignoni, Carlos; Silva, Márcia V. da; Macedo, Alexandre J.
Abstract: The aim of this study was to select and identify thermophilic bacteria from Caatinga biome (Brazil) able to produce thermoactive keratinases and characterize the keratinase produced by the selected isolate. After enrichment in keratin culture media, an Anoxybacillus caldiproteolyticus PC2 was isolated. This thermotolerant isolate presents a remarkable feature producing a thermostable keratinase at 60°C. The partially purified keratinase, identified as a thermolysin‐like peptidase, was active at a pH range of 5.0–10.0 with maximal activity at a temperature range of 50–80°C. The optimal activity was observed at pH 7.0 and 50–60°C. These characteristics are potentially useful for biotechnological purposes such as processing and bioconversion of keratin.